Cardiac Implantable Electronic Device Implantation: Intraoperative, Acute, and Remote Complications. (October 2015) - Harding, Melissa E.
Abstract : Implantation of cardiac implantable electronic devices (CIEDs), including pacemakers, implantable cardioverter-defibrillators, and biventricular pacemakers/cardioverter-defibrillators, is becoming increasingly common with new implants now exceeding 1.5 million per year globally. As a result, health care providers in all disciplines are caring for an increasing number of patients with CIEDs. Although the risk of complications associated with implantation of CIEDs is relatively low, the sequela can be catastrophic. Management requires an understanding of an individual patient's indication for CIED implant, the steps of implant procedures, device function, and natural history of each complication.